2007
DOI: 10.2172/1036846
|View full text |Cite
|
Sign up to set email alerts
|

DOE Project on Heavy Vehicle Aerodynamic Drag

Abstract: ObjectiveClass 8 tractor-trailers consume 11-12% of the total US petroleum use. 1 At high way speeds, 65% of the energy expenditure for a Class 8 truck is in overcoming aerodynamic drag. The project objective is to improve fuel economy of Class 8 tractor-trailers by providing guidance on methods of reducing drag by at least 25%. A 25% reduction in drag would present a 12% improvement in fuel economy at highway speeds, equivalent to about 130 midsize tanker ships per year. Specific goals include:• Provide guida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The literature on heavy trucks aerodynamics 27,[33][34][35][36][37]41 shows that airflow characteristics, including drag, turbulence, and pressure distribution, are highly dependent on the shape, size, and surface characteristics of the truck. The time-averaged drag coefficient returned by the two numerical models is, respectively, 0.578 6 0.002 and 0.605 6 0.002 for the SST k À x and BSL-RSM models.…”
Section: A Flow Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on heavy trucks aerodynamics 27,[33][34][35][36][37]41 shows that airflow characteristics, including drag, turbulence, and pressure distribution, are highly dependent on the shape, size, and surface characteristics of the truck. The time-averaged drag coefficient returned by the two numerical models is, respectively, 0.578 6 0.002 and 0.605 6 0.002 for the SST k À x and BSL-RSM models.…”
Section: A Flow Fieldmentioning
confidence: 99%
“…Compared to the GTS model, the GCM includes a tractor part and a trailer part separated by a space in between and other components, such as wheels and axles in the sub-trailer. The GCM has been considered in a number of aerodynamic studies, 27,[33][34][35][36] where the focus was mostly on drag-reduction solutions for fuel economy purposes and a few on the flow topology around the heavy truck model. 35 Additional realistic tractor-trailer geometries, slightly different from the GCM, were also considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, the model used is a generic conventional model (GCM) truck built on the geometry of modern current truck generation [17], [18]. Using SOLIDWORKS software, this model is designed by referring to the modern current truck generation.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The CFD analysis is focused on salt sprays from vehicle traffic using large trucks as the vehicles most likely to produce significant salt spray plumes to further investigate the geometric parameters defining the so-called "tunnel effects". (McCallen, et al, 2007) covers both CFD analysis and experimental tests with references. This effort and many others demonstrated that CFD is a useful engineering tool that can be applied to the study of the aerodynamics of vehicles.…”
Section: Introduction and Objectivesmentioning
confidence: 99%